Food industry wastes : assessment and recuperation of commodities - Kosseva, Maria R.; Webb, Colin, 1954- (Elsevier : Academic Press, 2013)
Food Industry Wastes: Assessment and Recuperation of Commodities presents emerging techniques and opportunities for the treatment of food wastes, the reduction of water footprint, and creating sustainable food systems. Written by a team of experts from around the world, this book will provide a key resource for implementing processes as well as giving researchers a starting point for the development of new options for the recuperation of these waste for community benefit. There were over 34 million tons of food waste generated in the US alone in 2009 - at a cost of approximately $43 billion. And while less than 3% of that waste was recovered and recycled, there is growing interest and development in finding ways to utilize this waste in ways that will not only reduce greenhouse gasses, but provide energy, and potentially provide resources for other purposes. Food waste is an area of focus for a wide range of related industries from food science to energy and engineeringThis international authoring team represents the leading edge in research and development Provides insights on leading areas of current research as well as looking toward future opportunities for reusing food waste.
Keywords: potravinářský průmysl; recyklace odpadu; druhotné suroviny; potravní ekologie; food industry and trade; waste rycycling; secondary raw materials; food ecology; elektronické knihy; electronic books